<span><span>√<span><span><span>(<span><span>3<span>x4</span></span><span>y3</span></span>)</span>2</span>⋅<span>(<span><span>6x</span>y</span>)</span></span></span><span><span><span><span>3<span>x4</span></span><span>y3</span></span>2</span>⋅<span><span>6x</span>y</span></span></span>Pull terms out from under the radical.<span><span><span>3<span>x4</span></span><span>y3</span></span><span>√<span><span>6x</span><span>y</span></span></span></span>
Answer:
23
hope it helped you!!
BTW, angle 1 + angle 2 = 180
3x - 4 = <span>3(-3) - 4 = -9 - 4 = -13
</span>3x - 4 = <span>3(-1.4) - 4 = -4.2 - 4 = -8.2
answer
range { -13, -8.2}</span>
It would be -15 as the answer